Infliximab regulates monocytes and regulatory T cells in Kawasaki disease. Issue 9 (25th June 2018) - Koizumi, Keiichi; Hoshiai, Minako; Katsumata, Nobuyuki; Toda, Takako; Kise, Hiroaki; Hasebe, Yohei; Kono, Yosuke; Sunaga, Yuto; Yoshizawa, Masashi; Watanabe, Atsushi; Kagami, Keiko; Abe, Masako; et al.
Abstract: Background: The effect of infliximab (IFX) on immune cells has not been fully reported in Kawasaki disease (KD). To investigate the mechanism of IFX in KD, we examined changes in the abundance of CD14 + CD16 + activated monocytes, regulatory T cells (Treg ) cells, and T‐helper type 17 (Th17) cells following treatment with IFX. Methods: We collected peripheral blood from patients with i.v. immunoglobulin (IVIG)‐resistant KD and analyzed absolute CD14 + CD16 + monocyte, Treg (CD4 + CD25 + FOXP3 + ) and Th17 cell (CD4 + IL‐17A + ) counts on flow cytometry. We also measured changes in serum soluble interleukin (IL)‐2 receptor (IL‐2R), IL‐6, and tumor necrosis factor (TNF)‐α on enzyme‐linked immunosorbent assay. Results: Treg cells and Th17 cells significantly increased after IFX treatment compared with baseline (126 ± 85 cells/μL vs 62 ± 53 cells/μL, P < 0.01; 100 ± 111 cells/μL vs 28 ± 27 cells/μL, P < 0.05, respectively). In contrast, in a subgroup of patients with CD14 + CD16 + monocytes above the normal range before IFX, the CD14 + CD16 + monocytes significantly decreased following IFX treatment (72 ± 51 cells/μL vs 242 ± 156 cells/μL, P < 0.05).. Serum TNF‐α did not change, but soluble IL‐2R and IL‐6 decreased after IFX treatment. Conclusion: IFX could downregulate activated monocytes and upregulate Treg cells towards the normal range. IFX treatment thus contributes to the process of attenuating inflammation in KD.